Surgical Emergencies in Intestinal Venous Malformations - Romo Muñoz, Martha Isabel; Bueno, Alba; De La Torre, Carlos; Cerezo, Vanesa Nuñez; Rebolledo, Bryant Noriega; Cervantes, Manuel Gomez; Dore, Mariela; Gomez, Javier Jimenez; Santamaria, Manuel Lopez; Martinez, Leopoldo; Lopez-Gutierrez, Juan Carlos (European Journal of Pediatric Surgery, 2018)
Background Venous malformations (VMs) can occur in any part of the body; however, the gastrointestinal tract is a frequent location. These are usually asymptomatic, thus, representing a challenge to diagnosis. Intestinal location of VMs can be associated with severe complications that ultimately require an emergency surgery. Our aim was to analyze all patients with an intestinal VM with special focus on those who required emergency surgery.Materials and Methods A retrospective study of patients presenting complication caused by intestinal VM was performed. Clinical records, associated anomalies, physical findings, and treatment were assessed.Results Twenty-one patients had a diagnosis of intestinal VM, 16 (76%) were associated to blue rubber bleb nevus syndrome (BRBNS) and 5 (24%) were isolated. Only four (19%) of the total cases presented an episode of acute abdomen with hemodynamic instability that required an emergency surgery. Findings included two gastrointestinal bleedings, one volvulus, and one intussusception of small bowel. All patients underwent an uneventful recovery and are presently doing well.Conclusion Intestinal VM can be challenging to diagnose in emergency situations, such as gastrointestinal situation or acute abdomen. The complications associated with it must be kept in mind, regardless of its low incidence.
Keywords: intestinal venous malformations; emergency surgery; gastrointestinal bleeding; intussusception; volvulus